Molecular characterization of Leishmania species isolated from cutaneous leishmaniasis in Yemen - Mahdy, M. A.; Al-Mekhlafi, H. M.; Al-Mekhlafi, A. M.; Lim, Y. A.; Bin Shuaib, N. O.; Azazy, A. A.; Mahmud, R. (Public Library of Science, 2010)
Background Cutaneous leishmaniasis (CL) is a neglected tropical disease endemic in the tropics and subtropics with a global yearly incidence of 1.5 million. Although CL is the most common form of leishmaniasis, which is responsible for 60 of DALYs lost due to tropical-cluster diseases prevalent in Yemen, available information is very limited. Methodology/Principal Findings This study was conducted to determine the molecular characterization of Leishmania species isolated from human cutaneous lesions in Yemen. Dermal scrapes were collected and examined for Leishmania amastigotes using the Giemsa staining technique. Amplification of the ribosomal internal transcribed spacer 1(ITS-1) gene was carried out using nested PCR and subsequent sequencing. The sequences from Leishmania isolates were subjected to phylogenetic analysis using the neighbor-joining and maximum parsimony methods. The trees identified Leishmania tropica from 16 isolates which were represented by two sequence types. The predominance of the anthroponotic species (i.e. L. tropica) indicates the probability of anthroponotic transmission of cutaneous leishmaniasis in Yemen. These findings will help public health authorities to build an effective control strategy taking into consideration personâto-person transmission as the main dynamic of transmission of CL.